Strategic technology management of Nokia Corporation 2003-2013 : faulty choices and the collapse of the handset business - Lubinaite, Sandra (2015)
This extended case study aims to analyze the strategic technology management of Nokia Corporation – how and why Nokia failed to ensure the position at the forefront of a disrupted mobile communications market between 2003 and 2013. For this research a total of 13 knowledgeable informants have been interviewed, representing industry experts, third-party developers, subcontractors and ex-Nokians with various functional backgrounds, ranging from software experts to business management and research. The analysis suggests that the technological, organizational and industrial factors are interconnected and causally linked to overall performance of Nokia Corporation. This study extends the path-dependency literature by providing an empirical example of a company whose crucial path-breaking technology choices were prevented because of established power-relations and dominating technology. It looks further to the theories of industry dynamics and market disruption, which in Nokia’s case resulted with the establishment of the new dominant design as a result of convergence of mobile communications, Internet and digital services. This study provides empirical evidence to the radical industry transformation when both core activities and core assets became obsolete. One of the main managerial implications point to the significance of the core technology expertise in the top management layer for the successful technology strategy and technological transition.